Late-stage tectonic evolution of the Al-Hajar Mountains, Oman: new constraints from Palaeogene sedimentary units and low-temperature thermochronometry - Amerigo Corradetti (14634901) (2019)
Mountain building in the Al-Hajar Mountains (NE Oman) occurred during two major shortening stages, related to the convergence between Africa–Arabia and Eurasia, separated by nearly 30 Ma of tectonic quiescence. Most of the shortening was accommodated during the Late Cretaceous, when northward subduction of the Neo-Tethys Ocean was followed by the ophiolites obduction on top of the former Mesozoic margin. This shortening event lasted until the latest Santonian – early Campanian. Maastrichtian to Eocene carbonates unconformably overlie the eroded nappes and seal the Cretaceous foredeep. These neo-autochthonous post-nappe sedimentary rocks were deformed, along with the underlying Cretaceous tectonic pile, during the second shortening event, itself including two main exhumation stages. In this study we combine remotely sensed structural data, seismic interpretation, field-based structural investigations and apatite (U–Th)/He (AHe) cooling ages to obtain new insights into the Cenozoic deformation stage. Seismic interpretation indicates the occurrence of a late Eocene flexural basin, later deformed by an Oligocene thrusting event, during which the post-nappe succession and the underlying Cretaceous nappes of the internal foredeep were uplifted. This stage was followed by folding of the post-nappe succession during the Miocene. AHe data from detrital siliciclastic deposits in the frontal area of the mountain chain provide cooling ages spanning from 17.3 to 42 Ma, consistent with available data for the structural culminations of Oman. Our work points out how renewal of flexural subsidence in the foredeep and uplift of the mountain belt were coeval processes, followed by layer-parallel shortening preceding final fold amplification.  Other information Published in: Geological Magazine License: http://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1017/S0016756819001250